PENINGKATAN READING INTEREST MELALUI PENDEKATAN TADOKU PADA MATA KULIAH DOKKAI II - Hakim, Ruri Fadhillah; Setiawati, Nia; Noverisa, Eva Jeniar (Universitas Negeri Jakarta, 2025)
This study aims to enhance university students’ reading interest through the Tadoku approach in the Dokkai II course at the Japanese Language Education Program, Universitas Negeri Jakarta. The background of this research is the low reading interest among students, which negatively affects their reading comprehension skills in Japanese. This study applied a mixed-method approach by combining quantitative and qualitative data collection. Data were obtained through pre- and post-intervention questionnaires and in-depth interviews. The intervention was carried out over 12 weeks using the Tadoku web platform, which allowed students to read texts based on their language proficiency level and interests. The findings revealed a significant improvement in students' reading motivation, reading speed, and vocabulary acquisition. Furthermore, students showed high interest in digital reading materials and Japanese cultural content. It is concluded that the Tadoku approach is effective in fostering students’ interest and ability in reading Japanese. This research contributes to the development of engaging, interest-based reading strategies in Japanese language education.